An experimental comparison of RC beam-column joints incorporating different splice methods in the beam. (December 2021) - Dabiri, Hamed; Kheyroddin, Ali
Abstract: Reinforcement ratio and bar splice methods have an indubitable effect on the behavior of RC beam-column joints. The present experimental study is focused on evaluating the influence of parameters including reinforcement ratio of beams, method and number of splices on the performance of RC beam-column joints under dynamic loads. To aim this goal, four RC beam-column joints with different numbers of forging (GPW) or mechanical splices (threaded couplers) in the longitudinal bars of beams were tested under cyclic and axial loads applied to beams and columns, respectively. Force-drift hysteresis curves are provided and seismic parameters including displacement ductility, absorbed energy and stiffness are investigated and discussed. More importantly, the results of this study are compared to the results of other specimens available in the literature with similar splice methods but different reinforcement ratio examined under the same loads in order to figure out the effect of reinforcement ratio on the performance of joints with bar splices. Results indicated that the joints incorporating forging method exhibited more appropriate response in comparison to those with threaded couplers by showing more ductility, absorbed energy and stiffness. Moreover, it was observed that reinforcement ratio does not significantly affect stiffness of the specimens with different numbers and types of splices whereas ductility and absorbed energy changes remarkably by changing types and numbers of spliced bars when reinforcement ratio alters.